2018
DOI: 10.1039/c8an01306c
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical applications of mid-infrared quantum cascade lasers – a review

Abstract: Quantum cascade lasers with high spectral power density and narrow band emission profiles provide novel access to biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 91 publications
0
42
0
Order By: Relevance
“…QCLs are now deployed for several applications [1], such as industrial process control, monitoring of pipeline leaks, emission control of pollutants and green-house gases, safety in workplaces and so on. In parallel, QCLs have been largely used in the research arena for breath analysis [2], study of gas kinetics in combustion processes [3], investigation of plasma [4] or supersonic expansion of gases [5] and precision spectroscopy [6]. In the latter respect QCLs were recognized early as excellent candidates for high-resolution applications because of a quantum noise limit of few hundred hertz [7].…”
Section: Introductionmentioning
confidence: 99%
“…QCLs are now deployed for several applications [1], such as industrial process control, monitoring of pipeline leaks, emission control of pollutants and green-house gases, safety in workplaces and so on. In parallel, QCLs have been largely used in the research arena for breath analysis [2], study of gas kinetics in combustion processes [3], investigation of plasma [4] or supersonic expansion of gases [5] and precision spectroscopy [6]. In the latter respect QCLs were recognized early as excellent candidates for high-resolution applications because of a quantum noise limit of few hundred hertz [7].…”
Section: Introductionmentioning
confidence: 99%
“…This finding highlights the prospect of using the transflection opto-fluidic interface in a future long-term implant. Table 4.1 compares the demonstrated results to other work using QCLs with respect to different measurement parameters such as the type of QCL, the wavenumber range, the environment of the substance and the concentrations measured [20]. In Figure 4.1 a visualization of the achieved glucose sensitivities related to the respective mean glucose concentration is presented.…”
Section: Long-term Stabilitymentioning
confidence: 98%
“…This fact hindered the selectivity for glucose in presence of other substances with absorption peaks in the same spectral region. Later experiments showed that this issue can be overcome with tunable external cavity (EC-) QCLs [15][16][17][18][19] and the method became a well established choice for the quantification of all sorts of substances in liquid environment in vitro [20].…”
Section: State Of the Art In Mid-infrared Based Glucose Monitoringmentioning
confidence: 99%
See 2 more Smart Citations